Research Theme Design and Problem Formulation in Quantitative and Qualitative Approaches (Methodological Review in Educational Research) - Mochamad Faidlul Abrori; Nasrullah Nasrullah (Demagogi: Journal of Social Sciences, Economics and Education, 2026)
This article conceptually discusses research theme design and problem formulation in quantitative and qualitative approaches. A research theme is understood as the central idea that serves as the primary direction of the entire research process, while the problem formulation is the operational form of the theme formulated in the form of research questions. The discussion shows that in quantitative research, the theme is designed based on a theoretical framework and previous empirical findings and is expressed in measurable variables, so the problem formulation is specific, operational, and allows for statistical hypothesis testing. Conversely, in qualitative research, the theme is more oriented toward understanding the meaning, process, and experience of the subject, making it flexible and contextual. While the problem formulation takes the form of open-ended questions that can evolve according to the dynamics of field findings. A comparison of the two approaches reveals fundamental differences in how they view reality, research objectives, data types, and analytical techniques used. This article emphasizes that accuracy in designing the theme and formulating the problem according to the chosen approach is key to research success, as it determines the alignment between the objectives, methods, data, and the meaning of the resulting findings.